Dictionary of Taoist Internal Alchemy - Pregadio, Fabrizio (Asian Studies E-Books Online, Collection 2025., 2025)
This dictionary offers a unique perspective on the vast and varied terminology of Taoist Internal Alchemy ( Neidan ). Drawing on major original texts and premodern lexicons, it provides translations, definitions, and usage examples for over a thousand terms common throughout the tradition. A comprehensive index of English equivalents allows readers to easily locate the corresponding Chinese terms. Beyond serving as a reference for those reading, studying, or translating Neidan texts, the dictionary's entries offer glimpses into the rich imagery and poetic language of Internal Alchemy. See Less